Effects of dietary fibers with different physicochemical properties on fermentation kinetics and microbial composition by fecal inoculum from lactating sows in vitro. (26th August 2020) - Pi, Yu; Hu, Jie; Bai, Yu; Wang, Zhibo; Wu, Yujun; Ye, Hao; Zhang, Shiyi; Tao, Shiyu; Xiao, Yingping; Han, Dandan; Ni, Dongjiao; Zou, Xinhua; et al.
Abstract: BACKGROUND: Efficient utilization of dietary fibers (DFs) is important for optimizing feed resource utilization and animal health. The aim of the current study was to assess the effects of DFs with varying physicochemical properties (bulky, viscous, and fermentable) on fermentation kinetics and microbial composition during in vitro fermentation by fecal inoculum from lactating sow. According to the physicochemical properties, three different DFs, lignocellulose (LC), modified cassava starch (MCS) and konjac flour (KF) were selected as bulky fiber, fermentable fiber and viscous fiber respectively. Gas production, short‐chain fatty acids (SCFAs) profiles and microbial composition were monitored during the fermentation. RESULTS: Results showed that the gas production in 72 h (GP72h ) ranked as: KF > MCS > LC ( P  < 0.05). The halftime of asymptotic gas production ranked as: KF < MCS = LC ( P  < 0.001). At 36 h of fermentation, MCS group showed higher concentrations of formic acid and lactate than LC and KF groups, whereas KF group showed higher concentrations of propionate and butyrate than LC and MCS groups ( P  < 0.05). At 72 h of fermentation, KF group showed higher concentrations of formic acid, lactate and propionate than LC and MCS groups, whereas MCS group showed higher concentrations of acetate and butyrate than LC and KF groups ( P  < 0.05). At 36 h of fermentation, Anaerovibrio and Erysipelatoclostridium abundances were higher in KF group, whereas Proteiniclasticum abundance was higher in MCS group. At 72 h of fermentation, the abundance of Fibrobacter in LC group was higher than that in MCS and KF groups. In addition, we also observed that the abundances of certain specific bacteria ( Anaerovibrio and Erysipelatoclostridium ) were closely related to the SCFAs production (propionate and butyrate) at different fermentation times. CONCLUSION: Collectively, the present study revealed that KF is a fast fermentation fiber which could produce propionate and butyrate rapidly, whereas LC is difficult to be fermented by bacteria. In addition, the fermentation of DFs with different physicochemical properties had divergent impacts on microbial composition and SCFA production. These findings deepen our understanding of the mechanisms of interaction between DFs and intestinal microbiota, and provide new ideas for the rational use of fiber resources in lactating sows. © 2020 Society of Chemical Industry